Invitro studies on electrospun polyurethane scaffolds / Isra Zulfiqar - Isra, Zulfiqar (2019)
Electrospun polyurethane scaffolds have been used in the past for neural cells and cartilage. They have been used effectively in growing tissues and mimicking the extracellular matrix. Polymer scaffolds are also more easily available when compared to natural materials such as collagen that need to be harvested from living organisms and this may raise ethical issues. For this reason, polyurethane can also be used with osteoblast cells instead of natural materials, due to their mechanical strength, durability, biodegradability and relative ease of availability. In this experiment, two types of polyurethane scaffolds were fabricated using electrospinning. One of the scaffolds has parallel fibers with 0-degree alignment while the other has non-parallel fibers with 45-degree alignment. The polyurethane scaffold with non-parallel fibers contains 93.3% Polyurethane and 6.7% Hydroxyapatite whereas the polyurethane scaffold with parallel fibers has 100% Polyurethane. The cells used were human fetal osteoblast cells (HFOB), they are capable of very quick cell divisions and differentiation under appropriate conditions. Throughout the study, the cell culture protocols were followed in the lab and the cell counting and cell viability assays were carried out frequently. The results of this experimental study will prove if the electrospun polyurethane scaffolds are biocompatible and allowed cell attachment. Furthermore, it can be concluded if the addition of 6.7% hydroxyapatite to the polyurethane scaffold will have any noticeable changes on cell growth and attachment when compared to the scaffold with 100% polyurethane. This is done to observe whether a 100% polymer scaffold or a polymer scaffold with some natural mineral content (hydroxyapatite) would be better for HFOB growth and proliferation.